Exploring locally developed ELT materials in the context of curriculum-based value education in China: challenges and solutions - Deng, Shiping; Wang, Xuemei (Frontiers in Psychology, 2023)
The development of locally developed English language teaching (ELT) materials is believed to be conducive to meeting the requirements of local language education policies and practices, and to enhance learners' agency. In China, in order to implement national educational policy of curriculum-based value education, many locally developed ELT materials have been recently developed. However, there is a paucity of empirical research concerning the actual effects of such materials in practice. This study presents an empirical study of a recently developed set of teaching materials in the context of curriculum-based value education by adopting an approach consisting of questionnaires and interviews to examine the attitudes and experiences of users of these materials. The findings revealed a range of challenges in the use of these materials, including issues related to language and content of the materials, the integration of ideological and value elements, and the development of multi-dimensional teaching materials. The article then proposes possible solutions from the perspectives of optimizing the writing community, carefully selecting teaching materials, innovating the integration of ideological and political elements, and improving the development of multi-dimensional teaching materials. A framework for the evaluation of locally developed ELT materials is also proposed, with the intention of offering a useful benchmark for enhancing the development of such materials.